Tongkonan as a Living Curriculum: Intergenerational Transmission of Torajan Cultural Knowledge through Spatial and Ritual Practices - Sanderan, Rannu; Tarrapa, Setrianto; Pasulu, Alpius (Harati: Jurnal Pendidikan Kristen, 2025)
A key example of how cultural spaces transmit indigenous knowledge is the concept of traditional house of the Toraja people, the tongkonan. To comprehend the educational and cultural role of the tongkonan, this research explores its structural and symbolic aspects, rituals, and communal practices. Using a qualitative and ethnographic approach, the data were collected from participant observation, interviews and interdisciplinary analysis. Results illuminate that architectural design and symbolic carving of the tongkonan serves as pedagogical tools, and rituals and intergenerational exchanges collectively contribute to cultural continuity and communal identity. Yet modernization and globalization pose significant threats to the longevity of these practices, thus requiring creative adaptations, including digital documentation, community and social driven initiatives, and sustainable tourism models. These efforts not only protect Torajan cultural resources but also provide lessons for other indigenous people confronting similar predicaments. This research emphasizes the significance of the combination of traditional knowledge and contemporary practice to offer a crucial to the survival of cultures in a modern world.